Examining the changes in the self-efficacy and pedagogical beliefs of preservice teachers in Japan - Wang, Ye; Yonezawa, Takashi; Yamasaki, Akane; Ko, James; Liu, Yijie; Kitayama, Yoshie (Frontiers in Education, 2024)
With the outbreak of the COVID pandemic, preservice teachers have experienced an unprecedented situation and faced various kinds of issues due to uncertain learning and teaching environments. As a result, they felt insecure and disappointed about their teaching performance during student teaching. Self-efficacy to teach and pedagogical beliefs are crucial elements that influence preservice teachers' teaching performance during student teaching and their professional development in the early stage. This study adopted a quantitative research method to examine the changes in the self-efficacy and pedagogical beliefs of preservice teachers after student teaching during the initial teacher education stage in the Japanese context and how preservice teachers' self-efficacy and pedagogical beliefs changed during the COVID-19 pandemic. A sample of 133 preservice primary teachers in a university in Western Japan was recruited in this study. Two structured surveys were used to collect the data, and factor analyses and paired t-tests were fitted. This study verified the validity and internal consistency of two surveys in the Japanese context. The results showed that the Japanese preservice teachers' self-efficacy made a steeper change after student teaching. Their pedagogical beliefs increased significantly, however, yielded a small effect. The results suggested that student teaching is an essential source of influence on preservice teachers' self-efficacy and pedagogical beliefs. This study contributes to the meaningful application of theories developed in the West to Japan by highlighting the Japanese educational context. This study provides implications for effectively reinforcing preservice teachers' self-efficacy and pedagogical beliefs through developing deeper reflection skills, thus supporting them to overcome various challenges in their future teaching careers.